Governability in Central Sulawesi: An Assessment of Government Capacity to Support Minorities of the Regional Representative of Central Sulawesi Province - Asrifai Asrifai (Publik : (Jurnal Ilmu Administrasi), 2021)
This article focuses on discussing governance, which is defined as the government's ability in governance. Governability is influenced by the number of parties, the degree of political polarization between parties, party participation in government, and the relationship between most of the parliament and the executive. This research was conducted using a qualitative method with a descriptive analytical approach that describes, describes, and analyzes the governability in Central Sulawesi after the election of governors and vice governors in 2015. Although it has the potential for divided government to occur in the Regional Government of Central Sulawesi because only 13 seats or 29% of 45 (forty-five) the number of seats in the Regional People's Representative Council (DPRD), but in fact throughout 2016-2020 it was running effectively. There has never been any rejection of government programs by the DPRD during the 2016-2020 government. An interesting finding in this research is that the capacity and background of the regional head from the regional head elections has a big role in building governance with the ability to establish communication and coordination with DPRD members. Regional heads with good capacities and a background in bureaucracy and politicians also influence the performance of local governments and are related to their relationship with the DPRD. The governor who governs and the interaction between the governor and the governed all contribute to governability, including the type of external influence